Ambient Intelligence - Software and applications 2nd International Symposium on Ambient Intelligence (ISAmI 2011) - Novais, Paulo; Preuveneers, Davy; Corchado, Juan Manuel (Advances in Intelligent and Soft Computing, 2011)
ISAmI is the International Symposium on Ambient Intelligence, and aims to bring together researchers from various disciplines that are interested in all aspects of Ambient Intelligence. The symposium provides a forum to present and discuss the latest results, innovative projects, new ideas and research directions, and to review current trends in this area.This volume presents the papers that have been accepted for the 2011 edition, both for the main event and workshop. The ISAmI workshop WoRIE promises to be a very interesting event that complements the regular program with an emerging topic on reliability of intelligent environments.